Analisa Koefisien Harga Satuan Tenaga Kerja Dilapangan Dengan Analisa SNI Struktur Bangunan Gedung - Ahmad Iqbal Alfarisi; Elvira Handayani; Kiki Rizky Amalia (Jurnal Talenta Sipil, 2022)
In the implementation of a project problems related to labor, wages and materials are important things that need to be taken into account. The smallest job if not supported by a well-qualified workforce and good quality materials, will not provide maximum and satisfactory results in a project. Even due to improper use of human resources can result in large losses on a project. This research was conducted to look for comparisons between the unit price coefficient of field labor in the reinforced concrete column with the coefficient values in the Indonesian National Standard Analysis (SNI). To look for a comparison of the unit price coefficient of work wages this research uses the Time and Motion Study method. The results of the study using the Time and Motion Study method showed that in the building column reviewed the unit price coefficient of work for 10kg of processing was 0.0505 workers 0.0900 ironmen and 0.0171 for foreman. The unit price coefficient of 1 M2 formisting is 0.0351 workers, 0.0682 carpenters, and 0.0158 foreman. The unit price coefficient for M3 concrete casting work is 0.1404 stonemason and 0.0714 foreman.